Pengaruh Perilaku Interaktivitas Live Streaming terhadap Purchase Intention pada Keputusan Pembelian Thrift Shop, melalui Literasi Ekonomi sebagai Variabel Mediasi Studi pada Generasi Z di Provinsi DKI Jakarta - RHI Muhammad Ibnu Hibban; Karuniana Dianta A. Sebayang; Saparuddin Mukhtar (PENG: Jurnal Ekonomi dan Manajemen, 2026)
This study aims to analyze the influence of live streaming interactivity and purchase intention on thrift shop product purchasing decisions, with economic literacy as a mediating variable among Generation Z in DKI Jakarta Province. The method used was a quantitative approach, with data collected through a questionnaire from 100 student respondents. Data analysis was conducted using Partial Least Square Structural Equation Modeling (PLS-SEM). The results showed that live streaming interactivity had a positive and significant effect on purchase decisions. Purchase intention also had a significant influence on thrift shop product purchasing decisions. However, economic literacy did not mediate the effect of live streaming interactivity or purchase intention on purchase decisions. These findings strengthen the application of the Theory of Planned Behavior (TPB) in understanding the digital consumption behavior of the younger generation and emphasize the importance of interactivity in live streaming marketing strategies for thrift products. This study provides theoretical contributions to the development of digital economic literacy and practical input for thrift shop businesses in designing more effective promotions.